EU biofuel policies in practise: A carbon map for Kalimantan and Sumatra - Mareike Lange (Kiel Institute for the World Economy (IfW), 2013)
It is still difficult for biofuel producers to proof the contribution of their biofuels to reducing carbon emissions because the production of biofuel feedstocks can cause land use change (LUC), which in turn causes carbon emissions. A carbon map can serve as a basis to proof such contribution. I show how to calculate a carbon map according to the sustainability requirements for biofuel production adopted by the European Commission (EU-RED) for Kalimantan and Sumatra in Indonesia. Based on the carbon map and the carbon balance of the production process I derive maps showing the possible emission savings that would be generated by biofuels based on palm if an area were to be converted to produce feedstock for this biodiesel options. I evaluate these maps according to the criterion contained in the EU-RED of 35% minimum emission savings for each biofuel option compared to its fossil alternative. In addition, to avoid indirect LUC effects of the EU-RED that might offset any contribution of biofuels to reducing carbon emissions, I argue that all agricultural production should be subject to sustainability assessments and that for an effective forest protection policies need to address the manifold drivers of deforestation in the country. In this effort, my resulting carbon maps can be the basis for a sustainable land use planning with a strategy to reactivate degraded areas that is binding for all agricultural production in the country.
Keywords: Q42; Q58; Q56; Q16; 330; biofuels; carbon emissions; Renewable Energy directive; carbon map; land use change; Indonesia